POLITIK IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA DI KAWASAN SOEMANTRI BROJONEGORO KOTA JAMBI - M. Wira Anshori; Jefri Al Kausar; Fajar Alan Syahrier; Galank Pratama; Mirza Sazeta (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The dynamics of policy implementation regarding street vendor (PKL) arrangement in the Soemantri Brojonegoro Area, Jambi City, are analyzed in this study through the lens of political implementation and power relations. This research primarily focuses on how interactions between key actors and informal negotiations influence the sustainability of the 'Pesona Kuliner Soemantri' strategic project. Utilizing a descriptive qualitative method, data were gathered through field observations, in-depth interviews, and documentation studies. The findings indicate that the implementation process does not proceed linearly but is characterized by a continuous contestation of interests. A phenomenon of 'pseudo-sustainability' was identified, where trader compliance with spatial regulations is often temporary and highly situational. This condition is significantly driven by the use of discretion by local law enforcement officers acting as street-level bureaucrats, who frequently opt for informal negotiations and compromises to maintain social stability and prevent open conflict. The unequal power relations between government authorities emphasizing urban aesthetics and traders striving for economic survival create a dynamic yet fragile negotiation space. The study concludes that the success of street vendor arrangement is heavily dependent on a shift from coercive approaches toward more inclusive and participatory governance. This research recommends the strengthening of dialogue mechanisms and the involvement of informal actors in every stage of public space policy decision-making to ensure long-term policy effectiveness.